From homemakers to breadwinners? How mandatory kindergarten affects maternal labour market outcomes - Selina Gangl; Martin Huber (Journal of Population Economics, 2025)
The majority of Swiss children attend mandatory and cost-free kindergarten at age four. We examine the effect of this policy on maternal labour market outcomes. Using administrative data from Switzerland, we exploit the birthday cut-off for kindergarten entry in the same or in the following year and apply a non-parametric regression discontinuity design (RDD). We find that mandatory kindergarten has a statistically significant positive effect on the labour market attachment of previously non-employed mothers, increasing their employment probability by 4 percentage points. In contrast, there are no significant effects on other groups or in the total sample of mothers.
Keywords: H40; J13; J18; J21; J22; 330; Mandatory kindergarten; Maternal employment; Regression discontinuity design